Early Detection And Management Of Diabetes: Evaluating The Contribution Of Laboratory And Nursing Services In Primary Care Settings (The Review of Diabetic Studies, 2024)
Diabetes mellitus is one of the most prevalent chronic non-communicable diseases worldwide and poses a serious challenge to public health systems, particularly in primary care settings. Early detection and effective management are critical to reducing complications, improving patient quality of life, and lowering long-term healthcare costs. Primary care plays a central role in diabetes control, where laboratory and nursing services act as the first line of prevention, diagnosis, monitoring, and patient education. This paper examines the contribution of laboratory and nursing services in the early detection and management of diabetes within primary care environments. It explores how timely laboratory investigations enable accurate diagnosis and disease monitoring, while nursing services support screening, patient education, lifestyle modification, medication adherence, and long-term follow-up. The study highlights challenges such as limited resources, workforce shortages, and gaps in coordination, particularly in low- and middle-income settings. The paper argues that strengthening laboratory capacity and empowering nursing professionals can significantly improve diabetes outcomes. Integrated, team-based care models are recommended as an effective strategy for enhancing early detection and sustained management of diabetes at the primary care level.